Effect of Primary Care–Based Education on Reassurance in Patients With Acute Low Back Pain - Angelita, Angelita; Jimmy, Jimmy (International Medical Journal Corp. Ltd, 2024)
Background: The literature surrounding the effect of primary care-based education on reassurance in patients with acute low back pain (LBP) reveals a complex interplay between patient perceptions, clinician behaviors, and educational interventions. In the foundational study by Holt and Pincus. Literature Review: The literature surrounding the effect of primary care-based education on reassurance in patients with acute low back pain (LBP) indicates that educational interventions play a crucial role in shaping patient perceptions and enhancing self-management capabilities. The foundational study by Holt and Pincus emphasizes the necessity of effective reassurance in managing musculoskeletal pain, particularly by conveying the benign nature of LBP, which can significantly reduce long-term disability and improve self-management. Conclusion: In conclusion, the collective findings from these studies underscore the critical importance of primary care-based education and reassurance in managing acute low back pain. Effective educational interventions not only enhance patient understanding and self-management but also address psychological factors that may influence recovery. Continued research is essential to optimize these educational strategies, ensuring they are tailored to meet the diverse needs of patients and improve overall health outcomes